Ideal Distance of Commands on EASYVR for Smart House Control - Achmad Iqbal; Risfendra Risfendra (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
In the recent years, technology make everything to do easier. Home automation is the system otomatization for smart home. This project aims to design an automatic system tool for smart home using arduino mega 2560 as a central controller, easyVR as sound processor, driver relay and power supply. After testing, the result of this project shows a design which able to control electronics at home using audio censor. The result shows that overall function is quite well and need about 2 seconds for activated load.